Somewhere Between Luck and Trust - Richards, Emilie (Detroit Gale Cengage Learning, 2013)
While serving eight months in prison, Christy Haviland gave birth to the child of the man who put her there. Smart as she is, she has never learned to read. And that's the least of her hurdles. Georgia Ferguson, a talented educator, receives a charm bracelet that may help her find the mother who abandoned her at birth. Does she want to follow the clues? Both women are at a crossroads a place where unlikely unions can be formed.
Keywords: Self-realization in women; Large type books; North Carolina; Fiction